2010
DOI: 10.1002/acr.20037
|View full text |Cite
|
Sign up to set email alerts
|

Neutropenia in patients receiving anti–tumor necrosis factor therapy

Abstract: Objective. To examine the rates of and risk factors for neutropenia together with the dynamics of neutrophil and other white cell subset counts in a cohort of patients treated with a tumor necrosis factor (TNF) inhibitor for inflammatory arthritis. Methods. We performed a retrospective cohort study examining the association between baseline demographics, clinical features, medications used, and development of neutropenia, and behavior of neutrophil and other white cell subset counts during TNF inhibitor therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 20 publications
4
72
1
5
Order By: Relevance
“…However, TNF-α upregulates the expression of proinflammatory cytokines involved in the differentiation and maturation of hematopoietic stem cells, and it is possible that TNF-α blockade mediates bone marrow failure by inhibiting stem cell differentiation. TNF-α has been shown to directly exert a complex and dual effect on neutrophils, accelerating apoptosis in some cells, yet prolonging the survival of others (Hastings et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, TNF-α upregulates the expression of proinflammatory cytokines involved in the differentiation and maturation of hematopoietic stem cells, and it is possible that TNF-α blockade mediates bone marrow failure by inhibiting stem cell differentiation. TNF-α has been shown to directly exert a complex and dual effect on neutrophils, accelerating apoptosis in some cells, yet prolonging the survival of others (Hastings et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-TNF is associated with development of neutropenia shortly after initiation of treatment [46][47][48]. Furthermore, previous studies have shown that RA patients are at an inherently increased risk of infection as a consequence of their disease [13][14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…This was noted to be transient and resolved with continued therapy [24]. Cytopenias have been reported in TNF-inhibitor trials, including thrombocytopenia, lymphocytopenia, and neutropenia [25,26]. These cytopenias are generally mild and transient.…”
Section: Laboratory Abnormalitiesmentioning
confidence: 98%